Comparing Robust Decision-Making and Dynamic Adaptive Policy Pathways for model-based decision support under deep uncertainty. (December 2016) - Kwakkel, Jan H.; Haasnoot, Marjolijn; Walker, Warren E.
Abstract: A variety of model-based approaches for supporting decision-making under deep uncertainty have been suggested, but they are rarely compared and contrasted. In this paper, we compare Robust Decision-Making with Dynamic Adaptive Policy Pathways. We apply both to a hypothetical case inspired by a river reach in the Rhine Delta of the Netherlands, and compare them with respect to the required tooling, the resulting decision relevant insights, and the resulting plans. The results indicate that the two approaches are complementary. Robust Decision-Making offers insights into conditions under which problems occur, and makes trade-offs transparent. The Dynamic Adaptive Policy Pathways approach emphasizes dynamic adaptation over time, and thus offers a natural way for handling the vulnerabilities identified through Robust Decision-Making. The application also makes clear that the analytical process of Robust Decision-Making is path-dependent and open ended: an analyst has to make many choices, for which Robust Decision-Making offers no direct guidance. Highlights: This paper compares Robust Decision-Making (RDM) and Dynamic Adaptive Policy Pathways (DAPP). RDM and DAPP have different merits, which highlight their complementarity. RDM has a clear analytical process and the application is reasonably straight forward. DAPP offers a convenient framework for designing plans for dynamic adaptation over time.